1994
DOI: 10.1007/bf03020657
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated onset of vecuronium neuromuscular block with pulmonary arterial administration

Abstract: The purpose of this study was to determine the onset times of vecuronium neuromuscular block administered into either the central circulation or a peripheral vein. One hundred and twenty adult patients with a pulmonary artery (PA) catheter were randomly divided into one of three groups with respect to the routes of vecuronium administration (n = 40 in each group). Anaesthesia was induced with midazolam 2.5 mg iv and fentanyl 10-50 micrograms.kg-1 iv and maintained with intermittent doses of fentanyl 50 microgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…It is possible however that the proximity of the orbicularis oculi to the central circulation compared with the adductor pollicis may compensate for the difference in blood flow and may have a role in accelerating the onset of neuromuscular block at the former. The onset of vecuronium-induced neuromuscular block in the adductor pollicis muscle was more rapid when the drug was injected into the central circulation, via a pulmonary artery catheter, than when the drug was given into a peripheral vein on the hand 12 .…”
Section: Figurementioning
confidence: 95%
“…It is possible however that the proximity of the orbicularis oculi to the central circulation compared with the adductor pollicis may compensate for the difference in blood flow and may have a role in accelerating the onset of neuromuscular block at the former. The onset of vecuronium-induced neuromuscular block in the adductor pollicis muscle was more rapid when the drug was injected into the central circulation, via a pulmonary artery catheter, than when the drug was given into a peripheral vein on the hand 12 .…”
Section: Figurementioning
confidence: 95%
“…Iwasaki et al 2 reported that the administration of vecuronium through a pulmonary artery catheter into the right atrium shortened the latent onset time by 11 seconds compared with 82 seconds when vecuronium was administered into the dorsal vein of the hand. Drug administration followed by a 20-mL saline flush may be comparable with drug administration into the right atrium.…”
Section: Discussionmentioning
confidence: 98%
“…Nitahara et al [13] investigated the effect of 20 mL saline bolus injection following 0.1 mg/kg vecuronium administered from a peripheral vein with elevation of extremity and found onset time of neuromuscular block as 128.3 seconds in the control and 104.6 seconds in the saline flush group. Iwasaki et al [14] compared administration of vecuronium from a pulmonary artery catheter to the right atrium, and administration from dorsal vein of the hand, and found the onset time as 82 seconds in dorsal vein administration and 11 seconds in administration to the right atrium. Similarly, in our study we found that onset time of drug effect was 50 seconds shorter in saline flush group than the control group.…”
Section: Discussionmentioning
confidence: 99%